Research on Operational Strategy Optimization of the Traditional Game Live Streaming Platform -- Take Huya Live Streaming as an Example - Li, Yuzhe; Wen, Junbo; Zou, Xiang (Transactions on Economics, Business and Management Research, 2024)
The Internet live broadcast platform is one of the key topics in today's research. The researchers found that the decline in benefits is a common phenomenon in the traditional live broadcasting industry. However, there is still a lack of unified explanation for the research of Internet platform operation strategy and how to break the game. Therefore, to make up for the research gap in the decline of benefits of traditional live streaming Internet platforms and put forward targeted insights. This study took Huya Live streaming as an example to explore the optimization of traditional game live streaming operation strategy. The research methods of this paper are as follows: Taking the Huya Live streaming platform as an example, this paper describes its business model, platform attributes, and differentiated competitive strategy, and uses SWOT analysis to analyze the competitive environment of the Huya live streaming platform. The study found that the Huya live-streaming platform faces challenges such as incomplete realization of traffic, single revenue channels, and fierce market competition. Therefore, two kinds of optimization strategies are proposed. That is the continuous optimization of content ecosystem construction, and firm adoption of mobile and diversified development strategies, and hope to provide valuable references for research in this field.